KONSEP RUJUK BILFI’LI PERSPEKTIF SYAIKH NAWAWI AL-BANTANI - Nursyamsudin Nursyamsudin; Wardah Nuroniyah; Azizahtul Khasanah (Mahkamah : Jurnal Kajian Hukum Islam, 2021)
Marriage is a contract whose elements include the justification of wāṭi, the implementation of the rights and obligations of husband and wife. However, this element is sometimes forgotten so that disputes arise which end in the word alāq. Jumhur (the majority) of scholars agree on the fall of alāq for free people with the right to reconcile with his wife while waiting for the 'iddah period. In the implementation of the reconciliation agreed upon by the Ulama, it is rujuk bilqauli, while rujuk bilfi'li there are still differences of opinion. Shaykh Nawawi al-Bantani is one of the leading Shafi'iyah scholars who forbid. The formulation of the problem from this research is, how is the concept of rujuk bilfi'li from the perspective of Shaykh Nawawi al-Bantani, how is the legal istinbaṭ methodology of Shaykh Nawawi al-Bantani, and is there any relevance to the Compilation of Islamic Law (KHI). The purpose of writing this research is to find out how the concept of rujuk bilfi'li from the perspective of Shaykh Nawawi al-Bantani, to know the istinbaṭ method used by Shaykh Nawawi al-Bantani, and to know its relevance to the Compilation of Islamic Law. This research is a type of literature study (library research) in the form of "qualitative-descriptive" with a socio-historical approach, examining characters and describing their thoughts in legal terms and legal products that are adapted to the applicable KHI law. According to Shaykh Nawawi al-Bantani, rujuk bilfi'li is haram, and the provisions for the implementation of reconciliation according to him cannot be carried out by bilfi'li, only bilqauli can be done. If done bilfi'li then dita'zir. The argument for strengthening the prohibition is on the basis of taġlîẓan (aggravating) and iḥtiyāṭ (prudence). The istinbaṭ method used by Shaykh Nawawi al-Bantani is ta'liq wa takhrij. The relevance of Shaykh Nawawi al-Bantani's opinion with the Compilation of Islamic Law is contained in the provisions for the implementation of rujuk, the terms and conditions for the implementation of rujuk bilqauli and the prohibition on the implementation of rujuk bilfi'li. Meanwhile, in the case of problems resulting from the implementation of the bilfi'li reconciliation, there is no relevance.